Relationship between sources of reproductive information and prevalence of risky sexual behaviour among secondary school adolescents in Thika West Sub-County, Kiambu County - Mureithi, Peris Murugi; Otieno, Dr. Syprine; Njoroge, Dr.Wachuka (Global Journal of Health Sciences, 2019)
Purpose: The purpose of this study was to determine the relationship between sources of reproductive information and prevalence of risky sexual behaviour among secondary school adolescents in Thika West Sub-County, Kiambu County. Methodology: The study used descriptive survey method to collect data. A sample of 400 respondents was considered, with their guidance and counselling teachers as the key informants. A stratified sampling technique was adopted in selection of the secondary schools within Thika west sub-county, Kiambu County. The study used the researcher administered questionnaire, interview schedules (KII) and focus group discussion (FGD) as the data collection instruments. Descriptive statistics such as mean, mode and percentages and inferential statistics such as chi square and binary logistic regression were applied. P valueâ‰¤0.05 was considered statistically significant. Results: The study showed significant relationship between sources of reproductive information and the prevalence of risky sexual behaviour among adolescents in Thika west sub-county. The study concluded that secondary school adolescents in Thika west sub-county engaged in risky sexual behaviours and lacked adequate reproductive information. Unique contribution to theory, practice and policy: The study suggests that adolescents should be equipped with information as early as possible, and be consistently made available through their lives in order to empower them in sexual decision making and reduce chances of engaging in risky sexual behaviour.